1993
DOI: 10.1056/nejm199305133281904
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Infection Caused by Leishmania tropica in Veterans of Operation Desert Storm

Abstract: _T.-AENY SEONL Oiv bitk). 4411itI A11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
152
0
4

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(165 citation statements)
references
References 34 publications
(5 reference statements)
5
152
0
4
Order By: Relevance
“…L. tropica, which usually causes CL, may occasionally cause VL. [18][19][20] L. infantum is the predominant visceralizing Leishmania species in the Mediterranean region. 4 The identification of L. infantum as the probable cause of VL in the Jenin region is supported by molecular characterization using PCR of leishmanial isolates from the bone marrow of In addition to the presence of a suitable animal reservoir, a survey of the sand fly fauna in the Jenin region (Abdeen and others, unpublished data) indicated that several sand fly species proven or suspected to be vectors of L. infantum in other parts of the Middle East and the Mediterranean are present in the district.…”
Section: Discussionmentioning
confidence: 99%
“…L. tropica, which usually causes CL, may occasionally cause VL. [18][19][20] L. infantum is the predominant visceralizing Leishmania species in the Mediterranean region. 4 The identification of L. infantum as the probable cause of VL in the Jenin region is supported by molecular characterization using PCR of leishmanial isolates from the bone marrow of In addition to the presence of a suitable animal reservoir, a survey of the sand fly fauna in the Jenin region (Abdeen and others, unpublished data) indicated that several sand fly species proven or suspected to be vectors of L. infantum in other parts of the Middle East and the Mediterranean are present in the district.…”
Section: Discussionmentioning
confidence: 99%
“…The potential different roles of A2 proteins may also be associated with the different sizes and abundance of these proteins because A2 proteins are much less abundant in L. mexicana than in L. donovani. 2 It is also noteworthy that there has been reports of visceral Leishmania infections caused by L. tropica, a cutaneous Leishmania species (23,24). Although the host physical and immune status can also play important roles in determining the outcome of Leishmania infection (24), it is not known what caused the pathogenic change of these L. tropica parasites.…”
mentioning
confidence: 99%
“…1985). Phlebotomus sergenti, the known vector for L. tropica transmission, has also been found in A1 Taif (Nadim et al 1979), where our patient worked. The belief that certain clinical profiles are assigned to specific Leishmania species has recently been challenged.…”
Section: Discussionmentioning
confidence: 52%
“…Visceral leishmaniasis caused by L. infantum has been found near Alexandria, in El Agamy (Awadalla et al 1987). Leishmania tropica, another causative species for cutaneous leishmaniasis, is widely distributed over the Middle East, especially in countries bordering the Arabian Gulf (Nadim et al 1979), but not in Egypt. In Saudi Arabia, L. tropica is endemic in the western and south-western part of the Kingdom (Peters et al 1985).…”
Section: Introductionmentioning
confidence: 99%